Kepatuhan Pengusaha Kena Pajak Sebelum dan Sesudah Penerapan Prepopulated Menu dan Pelaporan Web E-Faktur - Sofiana, Khusnurrosyidah; Somya L, Mienati; Okta Sindhu Hartadinata (Jurnal Akuntansi & Keuangan Unja, 2024)
Tax information systems are facing the growth of data technology systems, one of which is responding by changing tax invoices to e-faktur systems and continuing to make improvements in the system. On October 1, 2020, the Directorate General of Taxes launched improvements to e-faktur by adding the prepopulated menu and moving the Periodic Value Added Tax (VAT) tax return reporting through the e-faktur web. This study aims to determine differences in taxpayer compliance before and after the implementation of the prepopulated menu and e-faktur web reporting. The type of research used in this research is quantitative research using primary data through questionnaires and convenience sampling techniques. The results of the study show that there are indeed differences in taxpayer compliance before and after the implementation of the prepopulated menu and reporting via the e-faktur web. This research has novelty discuss regarding innovation in VAT reporting which is expected to provide implications that the prepopulated menu and e-faktur web reporting can increase the compliance of Taxable Entrepreneurs in fulfilling obligations related to VAT.